Nanoengineering neural stem cells on biomimetic substrates using magnetofection technology. Issue 41 (6th October 2016) - Adams, Christopher F.; Dickson, Andrew W.; Kuiper, Jan-Herman; Chari, Divya M.
Abstract : We demonstrate bioengineering of neural stem cells grown in physiologically relevant, neuromimetic hydrogels using magnetofection (translatable genetic engineering). Abstract : Tissue engineering studies are witnessing a major paradigm shift to cell culture on biomimetic materials that replicate native tissue features from which the cells are derived. Few studies have been performed in this regard for neural cells, particularly in nanomedicine. For example, platforms such as magnetic nanoparticles (MNPs) have proven efficient as multifunctional tools for cell tracking and genetic engineering of neural transplant populations. However, as far as we are aware, all current studies have been conducted using neural cells propagated on non-neuromimetic substrates that fail to represent the mechano-elastic properties of brain and spinal cord microenvironments. Accordingly, it can be predicted that such data is of less translational and physiological relevance than that derived from cells grown in neuromimetic environments. Therefore, we have performed the first test of magnetofection technology (enhancing MNP delivery using applied magnetic fields with significant potential for therapeutic application) and its utility in genetically engineering neural stem cells (NSCs; a population of high clinical relevance) propagated in biomimetic hydrogels. We demonstrate magnetic field application safely enhances MNP mediated transfection of NSCs grown as 3D spheroid structures in collagen which more closely replicates the intrinsic mechanical and structural properties of neural tissue than routinely used hard substrates. Further, as it is well known that MNP uptake is mediated by endocytosis we also investigated NSC membrane activity grown on both soft and hard substrates. Using high resolution scanning electron microscopy we were able to prove that NSCs display lower levels of membrane activity on soft substrates compared to hard, a finding which could have particular impact on MNP mediated engineering strategies of cells propagated in physiologically relevant systems.